In Memoriam, Fast Forward - Redfield, Marc (Surfaces, 1996)
This essay, a memorial tribute to Bill Readings, examines ways in which Readings' work refracts and reflects upon speed-a speed "prior" to reflection, representation, or measure. Readings' theorization of postmodern temporality is shown to be inseparable from his analysis and critique of late capitalism and the university.